Biotechnological Applications of Biogenic Nanomaterials from Red Seaweed: A Systematic Review (2014–2024) - Nunes, Aline [UNESP]; Rilievo, Graziano; Magro, Massimiliano; Maraschin, Marcelo; Vianello, Fabio; Lima, Giuseppina Pace Pereira [UNESP] (MDPI, 2025)
Green synthesized nanoparticles (NPs) are arousing constantly increasing attention due to inherent advantages such as biocompatibility, nontoxicity, and cost-effectiveness. As the state of the art of this rapidly evolving topic demands a punctual update, the present study was focused on reviewing the novelty, feasibility, and effectiveness related to the specific category of red seaweed-derived NPs. Among algae, red seaweeds have already gained consideration in the global market due to their high content of primary and secondary metabolites, supporting multifunctional applications across various industries. This scoping review reveals how this interest has also driven their investigation as a natural source for the sustainable NP fabrication. The fragmentary body of studies was synthesized, identifying red seaweed NPs as a flourishing nanotechnological subgroup and meriting their own space in the scientific literature. Noteworthy, the great majority of the reviewed papers feature efficient controlled release, enhanced bioavailability, and reduced toxicity, making red seaweed NPs elective candidates for the medical sector as anticancer, antimicrobial, and antioxidant agents. Moreover, their parent natural counterparts seem to endow NPs with unexpected specificity toward biological targets such as prokaryotic and tumor cells. Nanotechnological solutions based on red seaweeds pave the way to a new avenue of opportunities and challenges.